Characterization and discrimination of nasopharyngeal carcinoma and nasopharyngeal normal cell lines using confocal Raman microspectroscopy. Issue 5 (2011) - Ye, Yuhuang; Chen, Yang; Li, Yongzeng; Su, Ying; Zou, Changyan; Chen, Yanping; Ou, Lin; Chen, Rong; Zeng, Haishan
Abstract : Raman microspectroscopy can provide molecular-level information about the biochemical composition and structure of cells and tissues with excellent spatial resolution. In this study, Raman spectroscopy of individual cells from nasopharyngeal carcinoma cell lines C666-1, CNE2 and nasopharyngeal normal cell line NP69 are investigated for their differences. The spectral intensity ratio at 1449 and 1657 cm −1 with a decision line of I1449 /I1657 =1.10 can very easily separate the tumor and normal cell lines into two groups. Principal component analysis (PCA) and linear discriminant analysis (LDA) are also used to classify different cell lines and achieved a specificity and sensitivity of 100 and 90%, respectively. The results support the potential utility of Raman spectroscopy for nasopharyngeal diagnosis.